Hypothermia radical pelvic surgery - Salem A., Mario (2015)
The technique of hypothermie in 3 cases of Radical Sugery of the Pelvis is described. The patient's temperaturas, were lowered down to 26° C.; pulse and blood pressure decreased in direct relation to the fall in temperature. The pulse rate was 40 - 60 beats per minute and the hypotention between 80 - 40 mm/Hg. Systolic. The following ECG changes were observed: prolongation of QT; elevation of ST; minor modifications of the T were; wandering pacemaker. All these modifications were reversible when the patient's temperature returned to normal. Blood loss appears to be greatly reduced and in relation to the hypotention associated with the method. Warming is obtained by immersing the patient in a bath at 45°C. for 20 minutes. The post-operatory recovery is free of many of the undesirable side effects of current methods of anesthesia.